Genome sequence and characterization of the bcs clusters for the production of nanocellulose from the low pH resistant strain Komagataeibacter medellinensis ID13488. Issue 4 (22nd February 2019) - Hernández‐Arriaga, Ana M.; del Cerro, Carlos; Urbina, Leire; Eceiza, Arantxa; Corcuera, Mª Angeles; Retegi, Aloña; Auxiliadora Prieto, M.
Summary: Komagataeibacter medellinensis ID13488 (formerly Gluconacetobacter medellinensis ID13488) is able to produce crystalline bacterial cellulose (BC) under high acidic growth conditions. These abilities make this strain desirable for industrial BC production from acidic residues (e.g. wastes generated from cider production). To explore the molecular bases of the BC biosynthesis in this bacterium, the genome has been sequenced revealing a sequence of 3.4 Mb containing three putative plasmids of 38.1 kb (pKM01), 4.3 kb (pKM02) and 3.3 Kb (pKM03). Genome comparison analyses of K. medellinensis ID13488 with other cellulose‐producing related strains resulted in the identification of the bcs genes involved in the cellulose biosynthesis. Genes arrangement and composition of four bcs clusters ( bcs1, bcs2, bcs3 and bcs4 ) was studied by RT‐PCR, and their organization in four operons transcribed as four independent polycistronic mRNAs was determined. qRT‐PCR experiments demonstrated that mostly bcs1 and bcs4 are expressed under BC production conditions, suggesting that these operons direct the synthesis of BC. Genomic differences with the close related strain K. medellinensis NBRC 3288 unable to produce BC were also described and discussed. Abstract : Genome sequence and characterization of the bcs clusters for the production of nanocellulose from the low pH resistant strain Komagataeibacter medellinensis ID13488.